Three new species of Rasahus, with clarifications on the identities of three other Neotropical corsairs (Heteroptera: Reduviidae: Peiratinae) - Swanson, Daniel R. (Zootaxa, 2018)
Three new peiratine species in the genus Rasahus Amyot & Audinet-Serville, 1843 (Hemiptera: Heteroptera: Reduviidae: Peiratinae) are described: Rasahus nesiotes sp. nov. from Grand Bahama, Rasahus deliquus sp. nov. from Panama, and Rasahus abolitus sp. nov. from French Guiana. Rasahus castaneus Coscarón, 1983 is reported for the first time from French Guiana. The identity of Reduvius scutellaris Fabricius, 1787 is clarified, resulting in the following taxonomic and nomenclatural changes: Rasahus rufiventris (Walker, 1873) is considered a junior synonym of Rasahus scutellaris (Fabricius, 1787) stat. rev. et syn. nov., and Pirates myrmecinus Erichson, 1848 is resurrected and transferred, resulting in Rasahus myrmecinus (Erichson, 1848) stat. rev. et comb. nov. Most records of Rasahus scutellaris auct. (nec Fabricius) prior to this study remain indeterminate. Additionally, the peiratine fauna known from Panama and French Guiana are enumerated, and an updated key to the species of Rasahus is provided. Lastly, Pirates digramma Walker, 1873 (p. 102), tentatively considered to belong to Rasahus by previous authors, is discussed and transferred to Tydides Stål, 1866, resulting in Tydides digramma (Walker, 1873) comb. nov.